2008
DOI: 10.1111/j.1742-7843.2008.00290.x
|View full text |Cite
|
Sign up to set email alerts
|

Chloramphenicol‐Induced Oxidative Stress in Human Neutrophils

Abstract: The aim of this study was to evaluate the in vitro effect of chloramphenicol in order to determine its potential toxic effects on human neutrophils, by using assays of reactive oxygen species (ROS) determination, nitrite measurement and antioxidant systems. Chloramphenicol enabled the oxidative stress response of neutrophils and increased the ROS production at 2, 4, 8 and 16 μ g/ml, while ROS generation decreased at high concentrations (32 μ g/ml). The nitroblue tetrazolium assay shows that neutrophils incubat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…In Brazil, there is a lack of scientific data on the incidence of ETBF in the population; however, data show the incidence of these microorganisms in HIV-positive children (3.1%) (8) The use of chloramphenicol has been declining in many countries due to the toxicity of the drug, which causes intestinal disorders, depression and anemia. On the other hand, in our country, this drug is consumed widely and in our study a high rate of resistance was observed for this antimicrobial (7,12,26). According to the literature, in the regions where the drug is still used for the treatment of infections in which BFG is involved, levels of resistance to chloramphenicol are up to 11%, though not all authors considered intermediary resistance (7,20).…”
Section: Resultsmentioning
confidence: 91%
“…In Brazil, there is a lack of scientific data on the incidence of ETBF in the population; however, data show the incidence of these microorganisms in HIV-positive children (3.1%) (8) The use of chloramphenicol has been declining in many countries due to the toxicity of the drug, which causes intestinal disorders, depression and anemia. On the other hand, in our country, this drug is consumed widely and in our study a high rate of resistance was observed for this antimicrobial (7,12,26). According to the literature, in the regions where the drug is still used for the treatment of infections in which BFG is involved, levels of resistance to chloramphenicol are up to 11%, though not all authors considered intermediary resistance (7,20).…”
Section: Resultsmentioning
confidence: 91%
“…Chloramphenicol has been demonstrated to affect the oxidative state of cellular components by increasing the intracellular ROS, while the glutathione level decreased in neutrophils [94] [109].…”
Section: Discussionmentioning
confidence: 99%
“…Also tenoxicam-treated patients had a significant decrease in nitrite levels [93]. But chloramphenicol increases nitrite production in neutrophils incubated with a corresponding increase in antibiotic concentration [94]. Thus inhibition of NO production paid attention to the anti-inflammatory activity of erythromycin.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the nitroso moiety of nitroso-chloramphenicol was evidenced by the lack of DNA damage seen when nitroso-chloramphenicol was replaced by chloramphenicol. Paez et al (2008) found that chloramphenicol at concentrations of 2-16 μg/mL increased the production of reactive oxygen species (ROS) in isolated human neutrophils in vitro. The activity of SOD, CAT and diaphorase was increased at these concentrations.…”
Section: Bone Marrow Suppression and Aplastic Anaemiamentioning
confidence: 99%
“…It is relevant to note that multiple biotransformation routes, i.e. the nitroreductive one, as well as the CYP-mediated oxidative dehalogenation and the glutathionedependent dechlorination, are thought to generate oxygen and nitrogen radical species playing a pivotal role in a number of chloramphenicol-mediated adverse effects (Paez et al, 2008;Oyagbemi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%